A soldier at heart a memoir - Choo, Winston 1941-; Chua, Siew San; D'Silva, Judith (Landmark Books, 2021)
"Don't be a coward. What are you afraid of? Never mind if people do not take favourably to what you have to share. Just be honest and truthful, don't embellish but humbly present your story." This was how Winston Choo convinced himself to write this memoir. As a boy, all he wanted was to be a soldier. Never in his wildest dream did he imagine that he would, one day, have three stars on his shoulders. He tells how he was groomed by Dr Goh Keng Swee to lead the Singapore Armed Forces - and yet had to surmount hurdles within both the military and civilian administration. He relates how he shaped the structure, values and culture of the SAF by focusing on people and esprit de corps, and taking a strategic yet pragmatic approach. After 33 years being a man of war, he found himself once again handpicked, this time to be a man of peace - first in the diplomatic service, then as Chairman of the Singapore Red Cross. His novel experience of being ADC to President Yusof Ishak and his astute dealings with the military around the world for the SAF ensured his success in making friends for his homeland. Stricken with cancer, but ever disciplined and never ready to surrender, Winston Choo shares what keeps him soldiering on.